Association of Circulating Ceramides With Cardiac Structure and Function in the Community: The Framingham Heart Study - Chike C. Nwabuo; Meredith Duncan; Vanessa Xanthakis; Linda R. Peterson; Gary F. Mitchell; David McManus; Susan Cheng; Ramachandran S. Vasan (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background A higher circulating plasma ceramide ratio (C16:0/C24:0) is associated with an increased risk of heart failure, even after accounting for standard risk factors including lipid markers. However, the pathobiological mechanisms that underlie this association are incompletely understood. We tested the hypothesis that plasma ceramide ratio (C16:0/C24:0) is associated with adverse cardiac remodeling in the community. Methods and Results We evaluated 2652 Framingham Offspring Study participants (mean age, 66±9 years; 55% women) who attended their eighth examination cycle and underwent routine echocardiography and liquid chromatography–tandem mass spectrometry–based assays for circulating ceramide concentrations. We used multivariable linear regression models to relate C16:0/C24:0 (independent variable) to the following echocardiographic measures (dependent variables; separate models for each): left ventricular mass, left ventricular ejection fraction, left atrial emptying fraction, left atrial end‐systolic volume, E/e′ (a measure of left ventricular diastolic function), and left ventricular global circumferential and longitudinal strain by speckle‐tracking echocardiography. In multivariable‐adjusted analyses, higher C16:0/C24:0 per standard deviation increment was associated with lower left ventricular ejection fraction (0.991‐fold change in left ventricular ejection fraction; P=0.0004), worse global circumferential strain (β=0.34, P=0.004), higher left atrial end‐systolic volume (β=2.48, p<0.0001), and lower left atrial emptying fraction (0.99‐fold change; P<0.0001). The C16:0/C24:0 ratio was not associated with either E/e′ or global longitudinal strain, and the association with higher left ventricular mass was rendered statistically nonsignificant upon correction for multiple comparisons. Conclusions Our cross‐sectional observations in a large community‐based sample are consistent with a potential detrimental impact of higher ceramide ratio (C16:0/24:0) on cardiac remodeling traits, which may partly explain the associations of these molecular species with clinical heart failure.